The incidence of Demodex species in skin biopsy specimens diagnosed as actinic keratosis and nonmelanoma skin cancer - Karaman, Ulku; Sener, Serpil; Samdanci, Emine; Colak, Cemil; Sasmaz, Sezai (Walter de Gruyter Gmbh, 2010)
Background: The most common types of skin cancers include basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), which are grouped as non-melanoma skin cancers. Actinic keratosis (AK) is a precancerous lesion that may develop into SCC. The pilosebaceous follicle mites, Demodex folliculorum and Demodex brevis, inhabit most commonly and densely certain facial skin areas where BCC and SCC also develops most frequently. Objective: Determine the prevalence of Demodex species in skin biopsy specimens diagnosed as SCC, BCC, and AK. Method: Specimens of the patients whose reports were available were studied in terms of Demodex. The specimens were stained using Hematoxylin and Eosin, and evaluated for Demodex species positivity. Results: There were Demodex species in seven (38.9%) out of 18 AK cases, 12 (31.6%) out of 38 SCC cases, and 26 (44.8%) out of 58 BCC cases of this study. The rate of Demodex species in patients diagnosed SCC, BCC, and AK was found to be rather high. Conclusion: Demodex species should also be evaluated in the follow-up of the treatment of patients in SCC, BCC, and AK group.
Keywords: Actinic keratosis; basal cell carcinoma; Demodex species; squamous cell carcinoma